Antidepressant xerogenic medications and restoration rates - Rindal DB, Rush WA, Peters D, Maupome´ G. (Blackwell Synergy, 2005)
This report examines the association between xerogenic antidepressant medication use and dental restorations (a proxy for dental caries).